Recognizes Absolute Zero of Ratio-scale Data Using Sentence as A Template - Heru Santoso Wahito Nugroho; Ristya Widi Endah Yani (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
Abstract